2000
DOI: 10.1034/j.1398-9995.2000.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in hospital admissions for childhood asthma in Oslo, Norway, 1980–95

Abstract: The findings of increasing first admission rate as well as overall admission rate for acute asthma in children under 4 years of age, but decreasing readmissions as well as number of treatment days in hospital, probably reflect changes in the management of the disease, as well as an increasing prevalence of childhood asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
62
2
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 25 publications
18
62
2
5
Order By: Relevance
“…The median age of the hospitalized children decreased by 2 yrs during the study period [6]. Consistent with the findings of Norwegian studies [6,13], the results suggested that the onset of paediatric asthma has shifted to a younger age group. Conversely, annual admission rates are related to infection epidemics, especially in the youngest age groups [23].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The median age of the hospitalized children decreased by 2 yrs during the study period [6]. Consistent with the findings of Norwegian studies [6,13], the results suggested that the onset of paediatric asthma has shifted to a younger age group. Conversely, annual admission rates are related to infection epidemics, especially in the youngest age groups [23].…”
Section: Discussionsupporting
confidence: 80%
“…The reduction was clearest during the final years of the survey, which coincided with the increased use of inhaled steroids for paediatric asthma in the area. Similar to previous findings, admissions increased, almost ten-fold during the 10 yrs, among children aged v2 yrs [6,11,13]. The median age of the hospitalized children decreased by 2 yrs during the study period [6].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Constitui um sério problema de saúde pública em todo o mundo e tem sido motivo de muita discussão no meio científico, pois, apesar dos recentes avanços no conhecimento de sua patogênese, a prevalência, a morbidade e a mortalidade têm aumentado progressivamente nos últimos vinte anos [1][2][3] .…”
Section: Introductionunclassified